Evolution of follistatin in teleosts revealed through phylogenetic, genomic and expression analyses - Johnston, Ian Alistair; MacQueen, Daniel John (Development Genes and Evolution, 2008)
Follistatin (Fst) inhibits transforming growth factor-beta (TGF-B) proteins and is a known regulator of amniote myogenesis. Here, we used phylogenetic, genomic and experimental approaches to study its evolution in teleosts. Phylogenetic analyses suggested that one fst gene (fst1) is common to euteleosts, but a second gene (fst2) is conserved specifically within the Ostariophysi. Zebrafish fst1/2 respectively appear on chromosomes 5 and 10 in two genomic regions, each with conserved synteny to a single region in tetrapods. Interestingly, other teleosts have two corresponding chromosomal regions with a similar repertoire of paralogues. Phylogenetic reconstruction clustered these gene duplicates into two sister clades branching from tetrapod sequences. We suggest that an ancestral fst-containing chromosome was duplicated during the teleost whole genome duplication, but that fst2 was lost in lineages external to the Ostariophysi. We show that Fst1 of teleosts/mammals has evolved under strong purifying selection, but the N-terminal of Fst2 may have evolved under positive selection. Furthermore, the tissue-specific expression of zebrafish fst2 was restricted to fewer tissues compared to its paralogue and the single fst1 orthologue of Atlantic salmon (Salmo salar). Zebrafish fst1/2 may have subfunctionalized relative to non-duplicated vertebrate lineages, as several regions in the fst promoter of tetrapods were conserved with one paralogue, but not both. Finally, we examined the embryonic expression of fst1 in a teleost outside the Ostariophysi (Atlantic salmon). During segmentation, fst1 was expressed in the anterior somite compartment but was excluded from muscle progenitors that strongly expressed myogenic regulatory factors (MRFs). Later, fst1 was expressed in myogenic progenitors of the pectoral fin buds and also within the pax7(+) cell layer external to the myotome.